Pengaruh Gaya Kepemimpinan, Loyalitas Karyawan, Dan Beban Kerja Terhadap Kinerja Karyawan (Studi pada Guru dan Karyawan UPT SMAN Nawangan Pacitan) - Rindyantama, Adidha Fiqi; Astuti, Rini Juni (Universitas Muhammadiyah Yogyakarta, 2017)
This research is aimed to analyze the effects of Leadership style, Employees’ Loyalty, and Workload towards the employees’ working performance (a Study on Teachers and Employees in UPT SMAN Nawangan Pacitan). The subjects of this research is Teachers and Employees in UPT SMAN Nawangan Pacitan. In this research, the population are 50 respondents by using the saturated sampling or census. The analytical tool used is SPSS (Statistical Package for Social Science) version 21, by using the double linear regression method.Based on the analysis, the result shows that the leadership style, employees’ loyalty, and workload have positive and significant effect towards the employees’ working performance. The Leadership style and workload have positive and significant effects towards the employees’ loyalty.